2020
DOI: 10.4236/jcdsa.2020.102008
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Skin Protective Activity of a Dexpanthenol Containing Formula (BEPANTHEN<sup>®</sup>) in a Diaper Rash-Like Model

Abstract: Background: Dexpanthenol containing formula (BEPANTHEN ), formulated as a water in oil preparation, is currently widely marketed as a diaper care product aiming to protect baby's buttocks and repair diaper dermatitis. Dexpanthenol is a well-known moisturizer with barrier-improving properties and the oily phase of the water in oil preparation forms a lipophilic film on the skin surface that isolates the skin from irritants (feces and urine). Prolonged contact with irritants triggers a local inflammation cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Over nine out of ten respondents reported that their babies experienced less nappy-related discomfort, crying, fidgeting and sleep disruption after applying the product. This correlates with previous clinical studies demonstrating that the application of dexpanthenol-containing products is associated with higher rates of alleviation of nappy rash symptoms, as well as significantly lower frequencies of nappy rash occurrence when compared with usual hygiene care alone [27,28]. Interestingly, a relatively higher proportion of as-needed users reported reductions in nappy-related discomfort, compared with frequent users.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Over nine out of ten respondents reported that their babies experienced less nappy-related discomfort, crying, fidgeting and sleep disruption after applying the product. This correlates with previous clinical studies demonstrating that the application of dexpanthenol-containing products is associated with higher rates of alleviation of nappy rash symptoms, as well as significantly lower frequencies of nappy rash occurrence when compared with usual hygiene care alone [27,28]. Interestingly, a relatively higher proportion of as-needed users reported reductions in nappy-related discomfort, compared with frequent users.…”
Section: Discussionsupporting
confidence: 88%
“…The lipids mixture forms a lipophilic film on the skin surface that isolates the skin from irritants (urine and feces) and excess of moisture while replenishing the skin lipids. Water-in-oil preparation is considered by the experts as the preferred galenic formulation for IND preparations, it creates a barrier that is effective yet "breathable" [27]. By not being fully occlusive, it helps maintain healthy moisture levels in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The balm used in this study contains paraffin and petroleum jelly, which are both of hydrophobic character. Consequently, the ointment is able to hinder hydrophilic formulations and water-based solutions from spreading and prevents them from draining to the lower parts of the nasal cavity covered with respiratory mucosa ( Peltier et al, 2020 ). Other formulations such as water-based hydrogels would reduce the surface tension of the water-based drops at the tip of the catheter and, hence, could possibly drain to the rostral parts covered with respiratory mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Pantothenic acid is a constituent of coenzyme A, which catalyzes the synthesis of key components of the lipid layers of the skin that play a role in maintaining the skin's barrier function 17,19 . Topical dexpanthenol‐containing products have been shown to maintain and repair the skin barrier function, supporting the healing of skin and reducing inflammation, and to maintain hydration of the skin's outer layer, decreasing transepidermal water loss 4,19–22 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 These irritants, in turn, disrupt the structure of the skin, leading to local inflammation. 3,4 IDD is characterized by reddening or scaling of the skin, which if untreated can progress to exudative or ulcerated lesions. [5][6][7] The condition can cause considerable discomfort to the baby, and can be distressing both to the infant, negatively impacting sleep and behavior, 8,9 and to the caregiver.…”
Section: Introductionmentioning
confidence: 99%